2010
DOI: 10.1111/j.1365-2966.2010.16612.x
|View full text |Cite
|
Sign up to set email alerts
|

Fractal dimension as a measure of the scale of homogeneity

Abstract: In the multifractal analysis of the large-scale matter distribution, the scale of the transition to homogeneity is defined as the scale above which the fractal dimension (D q ) of the underlying point distribution is equal to the ambient dimension (D) of the space in which points are distributed. With the finite sized weakly clustered distribution of tracers obtained from galaxy redshift surveys it is difficult to achieve this equality. Recently Bagla et al. have defined the scale of homogeneity to be the scal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
111
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(124 citation statements)
references
References 53 publications
(71 reference statements)
11
111
2
Order By: Relevance
“…Thus, sufficient time has elapsed for the formation of large structures in the distant universe. This is qualitatively consistent with the existence of the Hercules-Corona Borealis Great Wall (Horváth et al 2014;Balazs et al 2015); its size of 7-10 Gly challenges the homogeneity assumption of the ΛCDM model, which predicts structures not larger than ∼ 1.21 Gly (Yadav et al 2010;Clowes et al 2013). Second, the Copernican Principle would suggest that we are not exactly at the center of the antineutrino star.…”
Section: Discussionsupporting
confidence: 59%
“…Thus, sufficient time has elapsed for the formation of large structures in the distant universe. This is qualitatively consistent with the existence of the Hercules-Corona Borealis Great Wall (Horváth et al 2014;Balazs et al 2015); its size of 7-10 Gly challenges the homogeneity assumption of the ΛCDM model, which predicts structures not larger than ∼ 1.21 Gly (Yadav et al 2010;Clowes et al 2013). Second, the Copernican Principle would suggest that we are not exactly at the center of the antineutrino star.…”
Section: Discussionsupporting
confidence: 59%
“…Therefore, the current value of λ is λ 0 ≈ 3700 Mpc ≈ 12 Gly. It is very interesting that this Yukawa interaction range and the sizes of the largest known cosmic structures (Clowes et al 2013;Horvath et al 2014;Balazs et al 2015) are of the same order, thereby hinting at the opportunity to resolve the formidable challenge lying in the fact that their sizes essentially exceed the previously reported epoch-independent scale of homogeneity ∼ 370 Mpc (Yadav et al 2010). The authors arrived at this underestimate by comparing the deviation of the fractal dimension, characterizing the distribution of matter, from 3 (dimensionality of space) to its statistical dispersion.…”
Section: Newtonian Approximation and Homogeneity Scalementioning
confidence: 99%
“…Bagla, Yadav & Seshadri (2008) showed that in the concordance model, the fractal dimension makes a rapid transition to values close to 3 at scales between 40 and 100 Mpc. Sarkar et al (2009) found the galaxy distribution to be homogeneous at length-scales greater than 70 h −1 Mpc, and Yadav, Bagla & Khandai (2010) estimated the upper limit to the scale of homogeneity as being close to 260 h −1 Mpc for the ΛCDM model. Söchting et al (2012) studied the Ultra Deep Catalogue of Galaxy Structures; the cluster catalogue contains 1780 structures covering the redshift range 0.2 < z < 3.0, spanning three orders of magnitude in luminosity (10 8 < L4 < 5 × 10 11 L⊙) and richness from eight to hundreds of galaxies.…”
Section: Distribution Of Grbs In {R θ ϕ} Spacementioning
confidence: 99%